A systematic review and research agenda of internalized sexual stigma in sexual minority individuals: Evidence from longitudinal and intervention studies - Nguyen, Josh; Anderson, Joel; Pepping, Christopher A. (Clinical psychology review, 2024)
Internalized sexual stigma is a well-established risk factor for poor mental health among sexual minority individuals. However, there has been no synthesis of the literature pertaining to risk and protective factors that influence the development of internalized sexual stigma over time. This systematic review presents findings from 31 studies addressing this question (n = 9192); 23 studies examined psychosocial and sociodemographic predictors of internalized sexual stigma among sexual minority individuals, and eight studies tested the effects of psychological interventions on internalized sexual stigma. Longitudinal studies highlight the stability of internalized sexual stigma over time, and the role of stigma and discrimination, proximal minority stressors (e.g., outness, concealment), and psychological factors (e.g., depressive and anxious symptoms, coping styles, and demoralization) in predicting subsequent internalized sexual stigma. Demographic factors appear to play only a limited role in predicting subsequent internalized sexual stigma. Finally, most intervention studies found no significant effects in reducing internalized sexual stigma, with three exceptions finding significant intervention effects among young sexual minority individuals. We conclude by outlining a theory-driven model of internalized stigma and a research agenda to test more nuanced models of internalized stigma that include multifactorial risk indices. •We evaluated studies testing determinants of sexual minority internalized stigma.•Distal and proximal stressors predict subsequent internalized sexual stigma.•Demographics, personality, and social factors are likely moderators.•There is limited evidence for current interventions to reduce internalized sexual stigma.•An ecological diathesis-stress model of internalized sexual stigma is proposed.